PERAN INDIVIDU DAN KOMUNITAS MELALUI KEKUASAAN DAN PENDIDIKAN DALAM KEBERHASILAN PEMBERDAYAAN MASYARAKAT - Hendrawardani, Blandina; Endang Syta Triana; Sotya Partiwi Ediwidjojo; Ari Sunardi; Kardianto Indra Purnomo (JURNAL ILMIAH EDUNOMIKA, 2025)
Community empowerment has become an important strategy in sustainable development, especially in enhancing the independence and welfare of the community. This study aims to analyze the influence of individual and community roles on the success of community empowerment with power and education as mediating variables. The research method uses a quantitative approach with survey techniques on 100 respondents involved in the empowerment program at the village level. The research instrument used a questionnaire with a Likert scale, and the data were analyzed using Structural Equation Modeling (SEM) to measure the direct and indirect effects between variables. The research results show that the roles of individuals and communities have a direct positive impact on the success of community empowerment. Moreover, power and education have proven to be mediators that strengthen the relationship between the roles of individuals and communities in community empowerment. These findings highlight the importance of collaboration between individuals, communities, participatory access to power, and education in driving the success of sustainable community empowerment. This research is expected to serve as a reference for village governments, community facilitators, and policymakers in designing integrated empowerment programs to improve the quality of life of the community in a self-reliant and participatory manner. Keywords : community empowerment, individual roles, community roles, power, education